Censorship and freedom of expression in Mexican regional music: violations of human rights in Mexico - Martínez Cárdenas, Brian Emmanuel; de la Rosa Rodríguez, Paola Iliana (DIXI, 2026)
Article 19 of the Universal Declaration of Human Rights (UN, 1948) guarantees freedom of expression without restrictions, including the dissemination of ideas through any media. However, in Mexico this right is frequently violated, particularly within the artistic sphere of regional Mexican music, where narcocorridos have been censored and stigmatized under the argument that they promote the glorification of crime. The central issue of this research lies in the criminalization of these musical expressions, which limits the artistic freedom of their creators. The objective of this study was to examine how censorship policies, legal frameworks, and social narratives have restricted the dissemination of narcocorridos. The methodology is documentary and exploratory in nature, with a legal and cultural approach, based on a review of national and international legislation on freedom of expression, the analysis of relevant censorship cases, and specialized literature on the social and cultural evolution of the narcocorrido. The findings indicate that censorship not only undermines fundamental rights but also reinforces prejudices and limits the critical and testimonial function of art. It is concluded that restricting these expressions on moral grounds impoverishes social debate and denies their value as reflections of social reality.
Keywords: censorship; freedom of expression; narcocorrido; human rights; Mexican legislation